Measuring Promotion and Prevention Orientations of Secondary School Students: It Is More Than Meets the Eye. (1st July 2016) - Hodis, Flaviu A.; Hattie, John A. C.; Hodis, Georgeta M.
Abstract : The General Regulatory Focus Measure has been used extensively in psychological research to gauge promotion and prevention orientations. Findings of this research show that for New Zealand secondary school students, the General Regulatory Focus Measure does not measure promotion and prevention as theoretically independent constructs.